Pengaruh Kompensasi Finansial, Kompensasi Non Finansial dan Motivasi Kerja Terhadap Prestasi Kerja Karyawan PDAM Tirtanadi Medan - Indri Anggraini; Saskia Saskia; Indra Syafii (CV. Publikasi Indonesia, 2022)
This study aims to determine the effect of financial compensation, non financial compensation and work motivation on the work performance of PDAM Tirtanadi Medan employees partially and simultaneously. The analytical technique used is multiple linear regression, with a sample 0f 154 people. The results of this study indicate that the financial compensation variable has a positive and significant effect on work performance. The results of this study indicate that the non financial compensation variable has a positive and significant effect on work performance. The results of this study indicate that the work motivation variable has a positive and significant effect on work performance. Financial compensation, non financial compensation and work motivation have a positive and significant effect on work performance.